The wishmakers - Whitesides, Tyler (Whitesides, Tyler. Wishmakers, 2018)
Ace unwittingly releases a genie from a peanut butter jar and gets unlimited wishes that he must learn to use with their consequences before all the world's cats and dogs turn into zombies who will eat mankind.